2017
DOI: 10.1104/pp.16.01038
|View full text |Cite
|
Sign up to set email alerts
|

The Liverwort, Marchantia, Drives Alternative Electron Flow Using a Flavodiiron Protein to Protect PSI

Abstract: The diffusion efficiency of oxygen in the atmosphere, like that of CO 2 , is approximately 10 4 times greater than that in aqueous environments. Consequently, terrestrial photosynthetic organisms need mechanisms to protect against potential oxidative damage. The liverwort Marchantia polymorpha, a basal land plant, has habitats where it is exposed to both water and the atmosphere. Furthermore, like cyanobacteria, M. polymorpha has genes encoding flavodiiron proteins (FLV). In cyanobacteria, FLVs mediate oxygen-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
91
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(93 citation statements)
references
References 60 publications
2
91
0
Order By: Relevance
“…In addition to this, Flvs functions to release electrons from PSI in cyanobacteria (Shimakawa et al ). In land plants, liverworts and mosses also have functional Flv protein to stimulate the oxidation of P700 (Gerotto et al , Shimakawa et al ). In the present study, we have extended the importance of Flv protein in ferns and gymnosperms for immediate oxidation of P700 against a sudden over‐accumulation of electrons in photosynthetic electron transport chain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to this, Flvs functions to release electrons from PSI in cyanobacteria (Shimakawa et al ). In land plants, liverworts and mosses also have functional Flv protein to stimulate the oxidation of P700 (Gerotto et al , Shimakawa et al ). In the present study, we have extended the importance of Flv protein in ferns and gymnosperms for immediate oxidation of P700 against a sudden over‐accumulation of electrons in photosynthetic electron transport chain.…”
Section: Resultsmentioning
confidence: 99%
“…The fully expanded leaves of 3‐ to 4‐week‐old plants were used for physiological measurements. Meanwhile, WT and Δ flv liverwort ( Marchantia polymorpha ) were also analyzed (Shimakawa et al ). A male accession of M .…”
Section: Methodsmentioning
confidence: 99%
“…In addition, Takagi et al (2016) found that the production of ROS such as superoxide and singlet oxygen is suppressed when P700 is kept in its oxidized form (P700 + ). In fact, the oxidation of P700 has been frequently observed in the photosynthetic organisms as a physiological response to excessive light conditions (Klughammer and Schreiber, 1994;Golding and Johnson, 2003;Shimakawa et al, 2017). Thus, P700 oxidation may lead to the alleviation of PSI photodamage by ROS in the thylakoid membranes.…”
Section: Discussionmentioning
confidence: 99%
“…While the role of Flv in driving O 2 photoreduction in a photosynthetic organism has been first demonstrated in cyanobacteria (Helman et al, 2003), recent studies performed in the moss P. patens (Gerotto et al, 2016) and liverwort (Shimakawa et al, 2017), and mainly based on chlorophyll fluorescence measurements, concluded that Flv drive alternative electron flow and protect PSI particularly under fluctuating light. However, there was no experimental evidence until now of an Flv-catalyzed O 2 photoreduction in microalgae (Curien et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the accumulation of Flv proteins in a Chlamydomonas reinhardtii mutant (pgrl1) lacking photosynthetic control due to a deficiency in CEF, it was suggested that Flvs are induced to catalyze O 2 photoreduction when PSI acceptors are overreduced (Dang et al, 2014). More recently, Flv mutants have been characterized in the moss Physcomitrella patens (Gerotto et al, 2016) and in the liverwort Marchantia (Shimakawa et al, 2017), showing that these proteins are involved in alternative electron flow and are required for growth of the moss under fluctuating light. However, so far there is no experimental evidence for a Flv-mediated oxygen photoreduction in eukaryotic microalgae (Curien et al, 2016).…”
mentioning
confidence: 99%